PENGARUH PEMBERIAN KULTUR BAKTERI SELULOLITIK MELALUI AIR MINUM SEBAGAI SUMBER PROBIOTIK TERHADAP KOMPOSISI FISIK KARKAS ITIK BALI - I K. V., Manubawa; Bidura, I G. N. G.; Utami, I. A. P. (Jurnal Peternakan Tropika; Vol 4 No 2 (2016), 2016)
This research has purpose to study the influence of giving cellulotic bacteria culture through drinking water as probiotic source to carcass physical composition of Balinese duck aged 8 weeks. Ducks that are used in this research were 54 Balinese ducks aged 1 day. Design used in this research is the Complete Random Design (CRD) with three treatments and six times of repetition. The three treatments are the ducks given drinking water without supplementation of cellulotic bacteria culture as control (A); drinking water with 0,20% cellulotic bacteria culture (B); and drinking water with 0,40% cellulotic bacteria culture (C). Variables that are observed are the percentage of carcass meat, percentage of carcass bone, percentage of carcass fat, and protein consumption. Research result shows that the giving of cellulotic bacteria culture as probiotic source at level of 0,20%-0,40% through drinking water shows the percentage of carcass meat at treatment (B) and (C) is significant (P 0,05) which is higher than control (A), the percentage of subcutan fat including skin at treatment (B) and (C) shows significant result (P 0,05) lower than control (A). From this research it can be concluded that the influence of giving cellulotic bacteria culture of buffalo rumen isolate as probiotic source through drinking water given at level of 0,20%-0,40% can increase the percentage of carcass meat and reducing the percentage of carcass fat of Balinese ducks aged 8 weeks.
Keywords: Probiotic, cellulotic bacteria, carcass physical composition, Bali duck